2011
DOI: 10.1510/icvts.2010.255588
|View full text |Cite
|
Sign up to set email alerts
|

Is prophylactic minitracheostomy beneficial in high-risk patients undergoing thoracotomy and lung resection?

Abstract: A best evidence topic in thoracic surgery was written according to a structured protocol. The question addressed was whether prophylactic minitracheostomy (PM) is beneficial in high-risk patients undergoing thoracotomy and lung resection. Altogether, 115 papers were found using the reported search, of which four represented the best evidence to answer the question. Three randomised controlled trials (RCT) compared a total of 161 patients who underwent thoracotomy and received either PM or standard postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
1
0
5
Order By: Relevance
“…Minitrakeotominin bu amaç ile kullanımının güvenli ve efektif olduğu bildirilmiştir. [1][2][3][4] Göğüs cerrahisi ve üst abdominal cerrahi geçiren ileri yaşlı, fonksiyonel kapasitesi kötü, acil ameliyata alınan, düşük mental kapasiteli, ameliyat öncesi sigara içime öyküsü olan ve kronik obstrüktif akciğer hastalığı (KOAH) olan hastalarda profilaktik olarak kullanılabilir. [1,2] Ayrıca ekstübasyon planlanan ve SR'si olan hastalarda ekstübasyon öncesi uygulanabilir.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Minitrakeotominin bu amaç ile kullanımının güvenli ve efektif olduğu bildirilmiştir. [1][2][3][4] Göğüs cerrahisi ve üst abdominal cerrahi geçiren ileri yaşlı, fonksiyonel kapasitesi kötü, acil ameliyata alınan, düşük mental kapasiteli, ameliyat öncesi sigara içime öyküsü olan ve kronik obstrüktif akciğer hastalığı (KOAH) olan hastalarda profilaktik olarak kullanılabilir. [1,2] Ayrıca ekstübasyon planlanan ve SR'si olan hastalarda ekstübasyon öncesi uygulanabilir.…”
Section: Discussionunclassified
“…[1] Sekresyon retansiyonu tedavisinde kullanılan diğer yöntemler ile karşılaştırıldığında minitrakeotominin avantajları şunlardır; lokal anestezi altında perkütanöz olarak uygulanabilir, eğitimi olmayan kişiler tarafından kolaylıkla tekrarlayan aspirasyonlar yapılabilir, sekresyonun etkili bir şekilde atılabilmesi için gerekli olan etkili öksürüğü provoke eder, kanülünün ince olması nedeni ile kenarından sekresyon atımına izin verir, hasta tarafından kolay tolere edilir, gerektiğinde kenarından entübasyon tüpünün geçişine izin verir, içinden yüksek konsantrasyonda oksijen verilmesine olanak sağlar, konuşma ve yutma etkilenmez. [1,4] Literatürde Mini-Trach II kullanımına bağlı komplikasyonlar bildirilmiştir. [3] En sık görülen komplikasyon kanama ve lokal hematomdur.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…In their report the prophylactic MT group had a significant reduction in sputum retention and postoperative atelectasis, along with a reduction (not significant) in the incidence of pneumonia and toilet broncoscopy. A recent report by Abdelaziz et al [49] underlines that prophylactic MT facilitates early and regular suctioning of the tracheobronchial tree, and that for high-risk patients it may be beneficial during the critical postoperative period in preventing complications associated with sputum retention. However, they reported that no studies have demonstrated a significant reduction in mortality, intensive care unit or hospital length of stay following MT.…”
Section: Preventing Postoperative Pulmonary Complications (Ppc)mentioning
confidence: 99%